Association between periodontitis, gestational diabetes mellitus and diabetes mellitus type 1 and 2 in pregnant women - Esteves Lima, Rafael Paschoal; Costa, Fernando Oliveira; Cota, Luis Otávio Miranda; Cyrino, Renata Magalhães (Journal of Health & Biological Sciences, 2015)
Introduction: Diabetes is considered a risk factor for periodontitis. However, it is possible that periodontitis induces a systemic inflammatory process which could initiate and propagate an insulin resistance. The aim of this study was to analyze the association between periodontitis, gestational diabetes mellitus (GDM), diabetes mellitus type 1 (DM 1) and diabetes mellitus type 2 (DM 2) in pregnant women. Methods: The sample consisted of studying 20 pregnant women with DM 1 or DM 2, 20 women with GDM and 40 pregnant women without any endocrinopathy. Periodontal examination included analysis of bleeding on probing (BOP), probing depth (PD) and clinical attachment level (CAL). Periodontitis was defined as the presence of four or more teeth with at least one site with PD ≥ 4 mm and CAL ≥ 3 mm with BOP associated in the same site. Results: Results demonstrated an association between GDM and high maternal age, body mass index (BMI) and hypertension. The prevalence of periodontitis observed was 55%, 40% and 42,5% for women with DM 1 or DM 2 (p=0,360), with GDM (p=0,853) and in the control group, respectively. Conclusions: The sample showed high prevalence of periodontitis; however, there was no significant difference between pregnant women with DM 1 or DM 2, women with GDM or pregnant women in the control group.